Potential of Induced Metabolic Bioluminescence Imaging to Uncover Metabolic Effects of Antiangiogenic Therapy in Tumors - Indraccolo, Stefano; Mueller-Klieser, Wolfgang (Frontiers in Oncology, 2016)
Tumor heterogeneity at the genetic level has been illustrated by a multitude of studies on the genomics of cancer, but whether tumors can be heterogeneous at the metabolic level is an issue which has been less systematically investigated so far. A burning related question is whether the metabolic features of tumors can change either following natural tumor progression (i.e. in primary tumors versus metastasis) or therapeutic interventions. In this regard, recent findings by independent teams indicate that anti-angiogenic drugs cause metabolic perturbations in tumors as well as metabolic adaptations associated with increased malignancy. Induced metabolic bioluminescence imaging (imBI) is an imaging technique which enables detection of key metabolites associated with glycolysis, including lactate, glucose, pyruvate and ATP in tumor sections. Signals captured by imBI can be used to visualize the topographic distribution of these metabolites and quantify their absolute amount. ImBI can be very useful for metabolic classification of tumors as well as to track metabolic changes in the glycolytic pathway associated with certain therapies. Imaging of the metabolic changes induced by anti-angiogenic drugs in tumors by imBI or other emerging technologies is a valuable tool to uncover molecular sensors engaged by metabolic stress and offers an opportunity to understand how metabolism-based approaches could improve cancer therapy.